Study on Commitment Schemes of Secure Multi-party Computation - Xiaoqiang Guo; Yan Yan; Lihong Li; Hong Wang (Institute of Advanced Engineering and Science, 2014)
The problem of secure multi-party computation(SMPC) is one of the most fundamental problems in information security. First, we introduce the basic concept of SMPC and four SMPC basic agreement: key distribution,oblivious transfer, bit commitment and zero knowledge proof. Secondly, we separately illustrate commitment schemes commitment transfer protocol, commitment sharing protocol and commitment multiplication protocol. Finally, we present unconditionally secure multi-party computation with a passive adversary, an active adversary, general adversary structures.